Pancreatic Surgery in Patients with Concomitant Liver Cirrhosis: A Single Centre Experience - Maggino, Laura; Landoni, Luca; Malleo, Giuseppe; Marchese, Tiziana; Mascetta, Giuseppe; Butturini, Giovanni; Salvia, Roberto; Bassi, Claudio (JOP. Journal of the Pancreas, 2013)
Context Liver cirrhosis is known to negatively affect the outcome of various types of surgery, but very poor data on the safety of pancreatic surgery in cirrhotic patients are available. As a consequence, a consensus on the operability of this subgroup of patients do not exist, and the fear of complications often results in the decision to avoid surgery. However, pancreatic surgery is presently the only curative option for malignant disease, and an aggressive tumor resection is therefore mandatory whenever possible. Only one published study has investigated the risk of pancreatic surgery in cirrhotic patients, concluding that whereas Child A patients display increased complications but a relatively low mortality, surgery in Child B patients should be avoided. Objective To investigate the outcome of cirrhotic patients who underwent surgery for a pancreatic disease at our institution. Methods Between 2003 and 2010, 53 patient with pancreatic pathology and concomitant liver cirrhosis came to our observation. Among these 17 were addressed to surgery. We retrospectively analyzed data about the clinical-pathological features of these patients, classified them on the basis of the Child score and evaluated the post-operative outcome. Fourteen patients were Child A, 3 Child B; 9 underwent a radical pancreatic resection, 6 a palliative procedure, 2 a laparoscopic abdominal exploration. The main indication for surgery was pancreatic adenocarcinoma (n=11). Results Among the 17 operated patients, 13 had a regular post-operative course (76%), 4 experienced a complication (24%). Only 1 patient (6%) died due to surgery-related complications. The mean post-operative hospital stay was 9.2 days. Significantly, all the Child B patients had a regular post-operative course. Conclusions In our experience, the presence of liver cirrhosis, even Child B cirrhosis, is not an absolute contraindication for pancreatic surgery. A careful preoperative selection and an adequate post-operative care can offer an acceptable clinical outcome even in those patients usually considered not eligible for surgery.